CORPORATE GOVERNANCE COMPLIANCE AND FIRM VALUE: EVIDENCE FROM INDIAN MSMEs - Maddileti, Sravani; S, Dr. Gautami (International Journal For Research In Business, Management And Accounting, 2026)
Corporate governance has traditionally been associated with large, publicly listed corporations. However, its relevance to Micro, Small and Medium Enterprises (MSMEs) is increasingly recognized, particularly in emerging economies. Although MSMEs often operate under owner-managed structures with minimal separation between ownership and control, governance mechanisms remain essential for ensuring transparency, accountability, access to finance, and sustainable growth. This study conceptually examines the applicability of corporate governance principles to MSMEs. It analyses the theoretical foundations of governance, including agency theory and stakeholder theory, and evaluates how governance structures can enhance managerial efficiency, reduce financial constraints, and support long-term expansion. The paper also explores the transition of MSMEs into larger enterprises through structured governance mechanisms. The findings suggest that the adoption of governance practices, even in simplified forms, significantly strengthens the managerial and financial foundation of MSMEs.